3(x-2)-15=0

Simple and best practice solution for 3(x-2)-15=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-2)-15=0 equation:


Simplifying
3(x + -2) + -15 = 0

Reorder the terms:
3(-2 + x) + -15 = 0
(-2 * 3 + x * 3) + -15 = 0
(-6 + 3x) + -15 = 0

Reorder the terms:
-6 + -15 + 3x = 0

Combine like terms: -6 + -15 = -21
-21 + 3x = 0

Solving
-21 + 3x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '21' to each side of the equation.
-21 + 21 + 3x = 0 + 21

Combine like terms: -21 + 21 = 0
0 + 3x = 0 + 21
3x = 0 + 21

Combine like terms: 0 + 21 = 21
3x = 21

Divide each side by '3'.
x = 7

Simplifying
x = 7

See similar equations:

| 7x-9x+2=-4x+6 | | 27-11=2(x-2) | | -9.6+y=29 | | 24=2k | | x+25+4x=-21-4x-26 | | 11(10-4x)-5(15+15x)=868 | | 11=3x-7 | | 2(2s+1)+6(2-s)+3(3s-1)=-3 | | -12x-20=-10x+90 | | -100=-4y | | 19-6x=8+5x | | -18u=-180 | | 8x-8=9x+5 | | 5x^2+1=37 | | 8x+12-3x=29 | | 4.25y+15=-17 | | 0.6x=0.9 | | -3(x-2)=-8(-3x-8) | | -(5y+3)-(-4y-8)=-2 | | 0.5x+2=2x-4 | | 4(y-5)+2(y-2)=3(y-3) | | 2r^2+r-14=0 | | -2=9x-5 | | 9(3-5y)+45y=27 | | 4+2z-1=9z+21-5z | | 35-7q=-8 | | -5x+7=37 | | 27=6y^3 | | 38=8-14p | | 3(2-x)+4=5-(3x-10)-x | | -38=-8a-30 | | 5p+9p=28 |

Equations solver categories